A noise reduction method for force measurements in water entry experiments based on the Ensemble Empirical Mode Decomposition. (1st April 2022) - Spinosa, Emanuele; Iafrati, Alessandro
Abstract: In this paper a denoising strategy based on the EEMD (Ensemble Empirical Mode Decomposition) is used to reduce the background noise in non-stationary signals, which represent the forces measured in scaled model testing of the emergency water landing of aircraft, generally referred to as ditching. Fuselage ditching tests are performed at a constant horizontal speed of 12 m/s with a controlled vertical motion, resulting in a vertical velocity at the beginning of the impact of 0.45 m/s. The measured data are affected by a large amplitude broadband noise, which has both a mechanical and an electronic origin. The noise sources cannot be easily avoided or removed, since they are associated with the vibrations of the structure of the towing carriage and with the interaction between the measurement chain and the electromagnetic fields. The EEMD noise reduction method is based on the decomposition of the signal into modes and on its partial reconstruction using the residue, the signal-dominant modes and some further modes treated with a thresholding technique, which helps to retain some of the sharp features of the signal. The strategy is developed and tested first on a synthetic signal with a superimposed and known background noise. The method is then verified on the measurement of the inertial force acting on the fuselage when it is moving in air, as in this case the added mass is negligible and the denoised force should equal the product of the mass and the acceleration, both of them being known. Finally, the procedure is applied to denoise the forces measured during the actual ditching experiment. The results are superior to those obtained from other classical filtering methods, such as a moving average filter and a low-pass FIR filter, particularly due to the enhanced capabilities of the EEMD-denoising strategy here developed to preserve the sharp features of the signals and to reduce the residual low-frequency oscillations of spurious origin. Highlights: Force measurements in water-entry tests are performed to study aircraft ditching. The transient force measurements and the background noise are non-stationary signals. EEMD is used to reduce the noise using a partial reconstruction with selected modes. Interval thresholding is also employed to preserve the sharp variations in some modes. The EEMD-based denoising provides superior results compared to classical filters.